Physiotherapeutic evaluation and intervention proposal on a patient with post-chikungunya chronic arthritis - Oliveia, Abner Vin?cius Rolim de (Elsevier, 2021)
Background: Chikungunya fever is an arboviral disease characterized by a high morbidity rate related to intense and persistent arthralgia, causing a decrease in both quality of life (QoL) and productivity. This study aimed to report functional evaluation and multimodal physiotherapeutic intervention on a patient with post-chikungunya chronic arthritis (PCCA). Case presentation: Woman, 47 years old, resident of the municipality of Bel?m, state of Par?, northern Brazil, with clinical diagnosis of chikungunya fever marked by fever, swelling, pain in the joints of the hands and feet, and headache. The physiotherapeutic treatment started three months after the diagnosis and consisted of 24 sessions composed of electrotherapy, thermotherapy, and kinesiotherapy resources. The patient progressed from an initial status of intense pain in several joints to low pain in a single joint and showed improvement in all domains of QoL, mainly in limitations by physical and emotional aspects and functional capacity. Conclusions: This case report details a proposal of multimodal physiotherapeutic intervention for a patient with functional impairments due to PCCA, suggesting that the use of physiotherapeutic resources may help this process and bring some assistance to those affected by the disease.